2014
DOI: 10.1021/ja411568a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanisms of Direct Pyrrole Synthesis via Dehydrogenative Coupling Mediated by PNP-Ir or PNN-Ru Pincer Complexes: Crucial Role of Proton-Transfer Shuttles in the PNP-Ir System

Abstract: Kempe et al. and Milstein et al. have recently advanced the dehydrogenative coupling methodology to synthesize pyrroles from secondary alcohols (e.g., 3) and β-amino alcohols (e.g., 4), using PNP-Ir (1) and PNN-Ru (2) pincer complexes, respectively. We herein present a DFT study to characterize the catalytic mechanism of these reactions. After precatalyst activation to give active 1A/2A, the transformation proceeds via four stages: 1A/2A-catalyzed alcohol (3) dehydrogenation to give ketone (11), base-facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 172 publications
5
110
0
5
Order By: Relevance
“…68 It is important to recognize that commonly employed entropy evaluations within the rigid rotor, harmonic oscillator and ideal gas approximations normally overestimate the entropic cost for reactions occurring in solution phase, because ideal gas partition functions do not explicitly take into account hindered translation, rotation and vibration of the solute surrounded by solvent molecules. 25,[69][70][71][72][73][74] For example, Huang and coworkers observed that the calculated standard activation entropy values (-T∆S ‡ calc) consistently overestimate the experimental -T∆S ‡ exp values by ~4-5 kcal/mol at 298K. 71,72 Liang and coworkers also observed that -T∆S ‡ exp values are 50-60% of the computed -T∆S ‡ calc, and in some cases activation entropic costs -T∆S ‡ exp are overestimated by ~11 kcal/mol.…”
Section: Methodsmentioning
confidence: 99%
“…68 It is important to recognize that commonly employed entropy evaluations within the rigid rotor, harmonic oscillator and ideal gas approximations normally overestimate the entropic cost for reactions occurring in solution phase, because ideal gas partition functions do not explicitly take into account hindered translation, rotation and vibration of the solute surrounded by solvent molecules. 25,[69][70][71][72][73][74] For example, Huang and coworkers observed that the calculated standard activation entropy values (-T∆S ‡ calc) consistently overestimate the experimental -T∆S ‡ exp values by ~4-5 kcal/mol at 298K. 71,72 Liang and coworkers also observed that -T∆S ‡ exp values are 50-60% of the computed -T∆S ‡ calc, and in some cases activation entropic costs -T∆S ‡ exp are overestimated by ~11 kcal/mol.…”
Section: Methodsmentioning
confidence: 99%
“…The splitting of the H-H bond then occurs via a proton/hydride transfer process with the formation of the Metal−H hydride and a C-H or N-H bond. Recent studies on hydrogen activation by Wang and Huang et al [74,96] show completely different thermodynamic preferences between the Ru pincer complexes with -NPR 2 (Ru16) and -CHPR 2 (MRu5) arms (Figure 4(a) and 4(b)). The H 2 cleavage by Ru16 is thermodynamically less favorable than that by the MRu5 system.…”
Section: Thermodynamic Considerationsmentioning
confidence: 94%
“…When using one water and one alcohol molecule as the shuttle, the barriers can be further dropped to 24.6 (TS8_W) and 21.9 kcal/mol (TS8_OL), respectively. [74,96]. A c c e p t e d M a n u s c r i p t Figure 9.…”
Section: Alcohol Dehydrogenation Via Metal-ligand Cooperationmentioning
confidence: 99%
See 2 more Smart Citations